Glenohumeral Microfracturing of Contained Glenohumeral Defects: Mid- to Long-term Outcome - Julia K. Frank, M.D; Philipp R. Heuberer, M.D; Brenda Laky, Ph.D; Werner Anderl, M.D; Leo Pauzenberger, M.D., Ph.D (Elsevier, 2020)
Purpose: To report mid- to long-term clinical and radiological outcomes after microfracturing for symptomatic chondral defects of the glenohumeral joint Methods: All patients who underwent glenohumeral arthroscopic microfracturing between 2002 and 2012 at a single center were considered for inclusion in this retrospective study. Clinical outcome was evaluated using the Constant Score, Oxford Shoulder Score, and Subjective Shoulder Value. Progression of joint space narrowing, sclerosis, marginal osteophytes, and presence of cysts over time were assessed using 4 different radiological grading systems Results: A total of 16 patients (n = 9 female, n = 7 male) with a mean age of 51.8 ± 12.6 years at the time of surgery and a mean follow-up of 122 ± 51.2 months (range, 61-204 months) were included in this retrospective study. Nine patients (56.3%) showed an isolated chondral defect, while 7 patients (43.8%) had concomitant pathologies. Constant Score (60.3 ± 12.7 vs. 85.9 ± 9.3; P < .001), Oxford Shoulder Score (29.0 ± 5.8 vs. 42.4 ± 4.5; P < .001), and Subjective Shoulder Value (23.9 ± 7.4 vs. 84.3 ± 10.9; P < .001) changed significantly from pre- to postoperative. The majority of patients (88%) were able to return to their preoperative level of activity. Three patients (19.8%) developed radiological signs of progressive glenohumeral degeneration during the study period. However, only 1 patient (6.25%) showed a progression of arthritic changes of more than 1 grade according to radiographic classifications. Two patients (12.5%) underwent revision surgery to a hemi shoulder arthroplasty during the study period at 12 and 36 months after the initial procedure Conclusions: Glenohumeral microfracturing is commonly performed together with other procedures, but seems to be a feasible treatment option for contained cartilage lesions in active patients reproducibly yielding good mid- to long-term outcome. Level of Evidence: Level IV, therapeutic case series.